2017
DOI: 10.1038/onc.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

CpG-based immunotherapy impairs antitumor activity of BRAF inhibitors in a B-cell-dependent manner

Abstract: Combining immunotherapy with targeted therapy has increasingly become an appealing therapeutic paradigm for cancer treatment due to its great potential for generating durable and synergistic antitumor response. In this study, however, we unexpectedly found that two types of CpG-based tumor peptide vaccine treatments consistently negated the antitumor activity of a selective BRAF inhibitor in tumors with BRAF mutation rather than showing a synergistic antitumor effect. Our further studies demonstrated that CpG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…A similar potentially antagonistic antitumor effect has been observed with the combination of immunotherapy and targeted therapy. In that, although both CpG-based tumor vaccine and BRAF inhibitor have therapeutic benefit as monotherapies in patients with cancer, combining CpG with BRAF inhibitor negates the antitumor effect of BRAF inhibitor in Braf-mutant tumors in a B-cell-dependent manner (38). Therefore, to develop potent therapeutic strategies for OX40-based cancer treatment, we need to not only rationally choose combination partners with complementing effects, but also optimize treatment schedules to maximize the antitumor effect of anti-OX40.…”
Section: Discussionmentioning
confidence: 99%
“…A similar potentially antagonistic antitumor effect has been observed with the combination of immunotherapy and targeted therapy. In that, although both CpG-based tumor vaccine and BRAF inhibitor have therapeutic benefit as monotherapies in patients with cancer, combining CpG with BRAF inhibitor negates the antitumor effect of BRAF inhibitor in Braf-mutant tumors in a B-cell-dependent manner (38). Therefore, to develop potent therapeutic strategies for OX40-based cancer treatment, we need to not only rationally choose combination partners with complementing effects, but also optimize treatment schedules to maximize the antitumor effect of anti-OX40.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the host immune system generating anti-cancer immune cells and antibodies [ 12 ] is one of the pillars of immune-based targeted therapies [ 13 , 14 ], as cell- and antibody-based drugs have been shown to inhibit cancer growth through different complementary mechanisms. However, there is growing evidence suggesting that B cells and antibodies can also be involved in tumor promotion and resistance to cancer therapy [ 15 , 16 , 17 ], with the observation that B cell depletion can suppress tumor growth in mice [ 18 ]. In ovarian cancer, the presence of CD20 + B cells has been associated with an increased survival, while in contrast, the presence of regulatory B cells (B regs ) induces immunosuppressive effects, supporting tumor growth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study verified that class A CpG ODNs enhanced NK cell cytotoxicity against Tu167 and K562 cell lines in vitro [45]. However, a few reports have indicated that CpG ODN treatments may not result in B cell-based antitumor activities [46,47]. Contrarily, TNFαsecreting B cells induced by ODN 2216 may show resistance to certain chemotherapies in mice models [46].…”
Section: Cpg Odn Classification and Antitumor Efficacymentioning
confidence: 97%
“…However, a few reports have indicated that CpG ODN treatments may not result in B cell-based antitumor activities [46,47]. Contrarily, TNFαsecreting B cells induced by ODN 2216 may show resistance to certain chemotherapies in mice models [46].…”
Section: Cpg Odn Classification and Antitumor Efficacymentioning
confidence: 99%